A estrutura da rede das companhias aéreas brasileiras: concentração empresarial e centralização territorial - Ana Paula Camilo Pereira (Confins)
The structure of the Brazilian aerial network has been configured in a concentrated and centralized way for decades. The concentration is due to the business performance, which is manifested by the flights performed by three major airlines. The centralization operates territorially with a densification of air connections at the main airports in the concentrated region of the country, thinning as it goes further. This relationship determines a network with little capillarity on the part of large airlines and focused around those airports that have traffic generation potential, showing that in Brazil there is a considerably extensive network of airports, but organized in a polarized way, defining a relationship with the structural trend of the Brazilian urban network. Thus, the objective of this article is to present an approach to the structure of the Brazilian air network through the analysis of the performance of airlines in 2019, thereby seeking to highlight the territorial power of the main Brazilian airlines that currently divide the national air market among themselves through operational strategies at airports with the greatest traffic potential.